Are regional airports economic effectiveness oriented? Evidence from Poland - Chwiłkowska-Kubala, Anna; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
Are regional airports economic effectiveness-oriented? Evidence from Poland Striving for a satisfactory level of effectiveness, managers must take actions aimed at achieving the set objectives and at reacting flexibly to changes that take place in the environment. They can do it by referring to the concept of dynamic capabilities that draw attention to a specific category of competences.
Keywords: economic effectiveness; dynamic capabilities; regional airports; efektywność ekonomiczna; dynamiczne możliwości; lotniska regionalne